Energy management and cost-benefit analysis of smart grid - Ren, Jiasheng (2017)
A single microgrid can only generate and distribute power within a localized area. Furthermore, in the event of unavailability/failure of one or more distributed energy resources (DERs) in the single microgrid during islanded mode of operation, the single microgrid itself may not be secure enough to meet its own load demand due to restricted energy generation capability. The additional power is required from utility grid or other microgrids in which they are in adjacent locations and interconnected to supply power to each other. Thus, an Energy Management System (EMS) is required to monitor, control, and optimize the generation, distribution and transmission of energy. This thesis presents a hierarchical architecture design for multi-microgrid using the Multi-Agent System concept to be incorporated into the Energy Management System. The optimum solution for the energy management is Mixed-Integer Linear Programming (MILP) to determine the minimum energy trading costs in the multi-microgrid system and the power balance within the multi-microgrid system is achieved through energy trading between different microgrids in a smart grid system.